Wing pattern in Zulia entreriana in Campo Grande, MS, Brazil - Koller, Wilson Werner; Valêrio, José Raul (Pesquisa Agropecuaria Brasileira, 2014)
An attempt was made in this work to characterize wing patterns (WP) of the spittlebug Zulia entreriana Berg, 1879 at a regional level, as well as to investigate sex-retio within these WPs. The adults collected every two weeks were classified based on the coloration pattern in six groups. The predominance of one particular sex within any WPs was always greater than 80% but naver was absolute. The predominance of males before and during the population peaks and of females after the population peaks caused differences in sex-ratios of adults collected on different dates. This explained the changes occurring in the frequencies of different PWs during the Study period.